Social-Religious Classes in the Society of Central Asia - Kalanov, Komil; Tukhtaev, Khakim; Kalanova, Sabokhat; Yokubova, Mavluda; Sadullaevna, 5Yusupova Hilola (International Journal of Psychosocial Rehabilitation, 2020)
Twenty-five years after its independence, Uzbekistan is looking for a new social model byintegrating old traditions, Islam and Modernity. Following a series of interviews conducted among Uzbeks in areas of South Kazakhstan and in some regions of Uzbekistan, the authors offer an indepth analysis of traditional social structures. After seventy years of the one-party system, “Western style” political parties are not as representative of social life as the khodjasare. Leadership in Uzbekistan is more social than political.